Nominal Group Technique Application Towards the Formation of Social Skills and Values Elements for Apprenticeship Competency Models - Yahaya, Norhayati; Rasul, Mohamad Sattar; Mohamad Yasin, Ruhizan; Sulaiman, Mohamad (Journal of Technical Education and Training, 2020)
Abstract is compulsory. This study discusses Nominal Group Technique as an alternative strategy for developing a list of social skills and values elements of the apprenticeship competency model. Social skills and values are some of the crucial parts of the TVET system and are to be considered as an additional incentive to the graduates. This study was conducted in the second phase (Development Stage) of researcherâ€™s research based on expertâ€™s consensus in identifying, accepting and ranking the social skills and values elements. The Modified Nominal Group Technique data analysis was determined based on the score given by all of the panels, of expertsâ€™ votes, which were converted into percentages and compared with the terms set. The expertsâ€™ agreement determined the final elements of social skills and social values. The voting process was aimed at determining the priorities of each of the element according to the preference of each expert that was based on individual scale interpretation. The Modified Nominal Technique group contains five stages: research briefings; idea generation; sharing and discussing ideas; voting through questionnaire; and presentation of findings. The findings of this study have identified a sum of 24 elements of social skills and values in the initial stage and finally, 20 elements of social skills and values were chosen as a component in the development of the model. In addition, the findings have shown that this technique has helped researchers to get the information effectively and rapidly due to the development of the model that can be obtained specifically through percentage score items tested based on expertsâ€™ consensus.